Global environmental governance: speeding up the debate on a world environment organization - Udo E. Simonis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
With the beginning of the new millennium, the longstanding need for reform of the United Nations system has gained new momentum. Efficiency gains and better coordination are desirable, though not sufficient to bring about improvement in international relations. There is need, therefore, to look for institutional innovations that would upgrade the pressing tasks of environmental and development policy in the eyes of national governments, international organizations, and nongovernmental organizations, improve the institutional setting for the negotiation and implementation of new agreements and action programs, and strengthen the action capacity of the developing countries on these matters. The present essay points to and elaborates the need . for global environmental governance with the help of a »World Environment and Development Organization» within the United Nations system, and outlines the shape it might be given.
Keywords: 300; Global environmental problems; capacity building for development and environmental protection; UN reform; WEDO; Internationale Umweltpolitik; Internationale Organisation; Reform; Entwicklungsorganisation; Welt